L’économie des ressources naturelles - Peterson, Frederick; Fisher, Anthony (L'Actualité économique, 1977)
AbstractA survey of the literature on the economics of natural resources. Extractive resources are classified as renewable or non-renewable, depending on whether they exhibit economically significant rates of regeneration. A unified model of optimal extraction over time is developed, drawing on a number of contributions to the literature. Special features are developed for the renewable and non-renewable cases, and extensions and applications are noted, as well as needs for further research. Policy issues are treated, chief among these being the extent to which the market can be trusted to generate the right rate of extraction. Finally the empirical evidence is reviewed on whether we are running out of extractive resources.